2012
DOI: 10.1152/ajplung.00406.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of allergic inflammation by supplementation with 5-hydroxytryptophan

Abstract: Clinical reports indicate that patients with allergy/asthma commonly have associated symptoms of anxiety/depression. Anxiety/depression can be reduced by 5-hydroxytryptophan (5-HTP) supplementation. However, it is not known whether 5-HTP reduces allergic inflammation. Therefore, we determined whether 5-HTP supplementation reduces allergic inflammation. We also determined whether 5-HTP decreases passage of leukocytes through the endothelial barrier by regulating endothelial cell function. For these studies, C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 123 publications
1
35
1
Order By: Relevance
“…In contrast to reports that support the role of serotonin in asthma, a negative correlation between plasma serotonin levels and the severity of asthma was reported by Abdala-Valencia et al, who showed that allergic inflammation was inhibited after the administration of 5-hydroxytryptophan, a serotonin precursor, in animal models of asthma [24].…”
Section: Discussioncontrasting
confidence: 65%
“…In contrast to reports that support the role of serotonin in asthma, a negative correlation between plasma serotonin levels and the severity of asthma was reported by Abdala-Valencia et al, who showed that allergic inflammation was inhibited after the administration of 5-hydroxytryptophan, a serotonin precursor, in animal models of asthma [24].…”
Section: Discussioncontrasting
confidence: 65%
“…In the kynurenine pathway, tryptophan is catalyzed into N-formylkynurenine by indoleamine 2,3 dioxygenase (IDO) and then converts into kynurenine. 5-HTP suppresses inflammatory responses in murine models of asthma and sepsis [ 11 , 12 ]. 5-HTP also inhibits the production of pro-inflammatory mediators in different cell lines [ 9 , 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…5-HTP taken orally was shown to suppress allergic lung inflammation even though cytokine levels were not decreased on bronchoalveolar lavage [ 12 ]. In the current study, we also found that 5-HTP did not affect the cytokine levels in the serum and the percentages of IFNγ + CD4 + T cells in the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5‐hydroxytryptophan (5(OH)Trp) is a tryptophan metabolite, which can be converted to serotonin (5‐hydroxytryptamine, 5‐HT), melatonin, or niacin. 5(OH)Trp had anti‐inflammatory effects in lipopolysaccharide‐induced sepsis, collagen‐induced arthritis and ovalbumin‐induced asthma in mice . The skin cells have the capability to transform tryptophan to 5(OH)Trp with further metabolism to serotonin, melatonin and other downstream metabolites .…”
Section: Introductionmentioning
confidence: 99%